Cognitive Pragmatics in Japanese Comic - Gultom, Eva Solina; Mersi, Muhammad Reza; Arman, Arman (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
Comics became one of the literary works that implemented communication practices that involved linguistics. This study examined the cognitive pragmatics in the Japanese comic, Your Lie in April, by Naoki Urusawa. This study was centered on cognitive pragmatics, encompassing elements of cooperation, mental states, intentionality, and motivation. This research employed the descriptive qualitative technique. Through the examination, the researcher found that the comic exhibits cognitive pragmatic elements in the characters of Arima and Kaori. These elements include cooperation, mental states, intentionality, and motivation. The researcher has discovered 21 cognitive pragmatic aspects comprising cooperation (5 data), mental states (6 data), intentionality (5 data), and motivation (5 data). The comic primarily focuses on mental states as the most significant cognitive pragmatic feature over other aspects. In conclusion, Arima and Kaori convey these qualities through their discussions and facial expressions.